Decolorization of orange II by immobilized thermotolerant white rot fungus Coriolus versicolor RC3 in packed-bed bioreactor - Srikanlayanukul M. (2014)
Immobilized Coriolus versicolor RC3, a thermotolerant white rot fungus, was investigated for Orange II decolorized capability both in batch and continuous system. In batch study, immobilized fungal cell was tried on 20 ppm Orange II dissolved in synthetic liquid medium using various carbon and nitrogen sources. One gram per liter of glucose without nitrogen source was a minimal carbon source level for providing the high decolorization rate. Optimal initial pH and temperature were 6.5 and 30-37°C, respectively. In continuous decolorization, packed bed bioreactor was designed to use with 2 g of immobilized fungal cells filled with synthetic liquid medium obtained from batch study. At 8 h of Hydraulic Retention Time (HRT), more than 90% of the decolorization was maintained over 120 h. Considering for the size of polyurethane foam (PUT), 1.5 cm3 PUT with 8 h of HRT could maintain a high efficiency and the decolorization duration increased to 2 weeks. After fungal decolorization, the toxicity of wastewater evaluated with Daphnia sp., normal and cancer cell lines were reduced completely. © 2008 Asian Network for Scientific Information.